Revealing the significance of early detection of chronic obstructive pulmonary disease: insights from healthy lung initiative data at COP27 conference - Wagdy Amin; Rasha Ashmawy; Sandy Sharaf; Sally Zeina; Esraa Abdellatif Hammouda; Nancy Mohamed; Rewan Gamal; Dina Abu Hamr; Heba Gebril; Ola Alaa; Ussama Taha; Hazem El-Feel (BMC Health Services Research, 2024)
Abstract Background Climate change poses a significant threat to respiratory health, exacerbating conditions like asthma, Chronic Obstructive Pulmonary Disease (COPD), and respiratory infections increasing morbidity and mortality indirectly through exposure to greenhouse gases. During the 27th Climate Change Conference (COP27), the Healthy Lung Initiative (HLI) for the early detection of COPD among smokers was launched in Egypt. Objective We aimed to detect the prevalence and predictors of confirmed COPD among smokers and assess physicians’ adherence to prescribing pulmonary function tests (PFTs) among the COP27 conference attendees. Methods This study utilized smokers’ data from the HLI, employing a cross-sectional design with an interview-based questionnaire, supplemented by spirometry for lung function evaluation. Participants, comprising Egyptian and non-Egyptian residents in Sharm El-Sheikh city, were provided with educational materials and encouraged to seek further evaluation from a pulmonologist. Results The HLI study, conducted from November 6th to 20th, 2022, involved 1133 participants, 90% (1047) of whom were smokers. Most smokers were males (96.3%) and Egyptians (98.6%), with half aged 30–39 and the majority starting smoking within the last 20 years. Despite common respiratory symptoms, 47% suffered from dyspnea on exertion, and only 4.3% have undergone lung function tests, suggesting a potential underdiagnosis of COPD. Most participants (82.6%) had an FEV1/FVC ratio > 70%, indicating no spirometry-confirmed COPD diagnosis, while 147 participants (17% of them) exhibited all three cardinal COPD symptoms simultaneously. Male gender and daily cigarette consumption were significant predictors for confirmed COPD, while age showed no significance in regression analyses. Conclusion The ongoing HLI focuses on early detection and education to combat smoking-related risks, particularly among middle-aged males, while also highlighting the need for comprehensive strategies to address the intersection of smoking and climate change.